Exercise and intervention: On the sociology of powerful knowledge (London Review of Education, 2019)
This article discusses John White's recent critique of the notion of 'powerful knowledge'. It is argued that White raises some salient points but overlooks the genesis of powerful knowledge as an idea and its debt to Durkheim and Bernstein. It is suggested that the work of Michael Young and others on powerful knowledge can be understood as both an exercise in the sociology of educational knowledge and an intervention in debates about the curriculum. Explicating the relationship between exercise and intervention sheds further light on White's critique and its subject matter.